2011
DOI: 10.4049/jimmunol.1004070
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Suppressor ARF Regulates Innate Immune Responses in Mice

Abstract: The innate immune system is the first line of defense against invading organisms, and TLRs are the main sensors of microbial components, initiating signaling pathways that induce the production of proinflammatory cytokines and type I IFNs. An antiviral action for the tumor suppressor alternative reading frame (ARF) has been reported; however, the precise role of ARF in innate immunity is unknown. In this study, we show that ARF plays an important role in regulation of inflammatory responses. In peritoneal macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 61 publications
3
40
0
3
Order By: Relevance
“…It could be argued that was assessed using MOG in a reconstituted system with increasing concentrations of H 2 O 2 . Following incubation at 37˚C, relative quantities of remaining substrate (MOG ) and cleavage products (MOG [42][43][44][45][46][47][48][49][50][51][52][53][54][55] and MOG [35][36][37][38][39][40][41] ) were quantified by reverse-phase HPLC following peak identification by MALDI-TOF MS. Data are presented as the abundance of the cleavage product MOG [42][43][44][45][46][47][48][49][50][51][52][53][54][55] relative to MOG (corresponding destruction of the I-A b binding region) and was calculated using the following formula: RPA = (P x /S x )/(P 0 /S 0 ), where RPA indicates relative peptide abundance; P x indicates product (MOG [42][43][44][45][46][47][48][49][50][51]…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It could be argued that was assessed using MOG in a reconstituted system with increasing concentrations of H 2 O 2 . Following incubation at 37˚C, relative quantities of remaining substrate (MOG ) and cleavage products (MOG [42][43][44][45][46][47][48][49][50][51][52][53][54][55] and MOG [35][36][37][38][39][40][41] ) were quantified by reverse-phase HPLC following peak identification by MALDI-TOF MS. Data are presented as the abundance of the cleavage product MOG [42][43][44][45][46][47][48][49][50][51][52][53][54][55] relative to MOG (corresponding destruction of the I-A b binding region) and was calculated using the following formula: RPA = (P x /S x )/(P 0 /S 0 ), where RPA indicates relative peptide abundance; P x indicates product (MOG [42][43][44][45][46][47][48][49][50][51]…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this, T cell hybridomas were first stably transfected with an NFA-T-enhanced IL-2 promoter-driven eGFP construct, followed by multiple rounds of selection by FACS to enrich those hybridoma clones that expressed eGFP only following presentation of their cognate peptide epitope by APCs (25). When added to BMMfs that were previously pulsed with HEL protein, we found that WT and Cybb 2/2 BMMfs were equally able to induce eGFP expression in two of the hybridomas (Hb1.9 and H46.13), indicating that the processing/presentation efficiency of HEL [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and HEL [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] peptides were unaffected by NOX2 (Fig. 2D).…”
Section: Nox2 Activity Influences Mhc-ii Presentation In An Ag-specifmentioning
confidence: 99%
See 3 more Smart Citations